Morphologic Changes of the 3-day-old Chick Embryos after Curcumin Exposure - Santiparadon, Manutsanun; Rongpan, Sudarat; Payanglee, Kolip; Hounkong, Kruawun; Koedpuech, Kasem (Princess of Naradhiwas University Journal, 2021)
Curcumin is a medicinal plant enlisted in the National List of Essential Medicines (Issue 2) B.E.2012, that has been used to treat flatulence, which is common in pregnancy especially during the first trimester. The aim of this study was to monitor morphological changes of the embryos in 3-day-old chicks exposed to curcumin 20, 40, and 60 mg/l. A total of 94 fertilized Rhode Thai eggs were divided into 5 groups: non-injection group, corn oil group, Cur-20, Cur-40 and Cur-60 received 0, 20, 40 and 60 mg/l of curcumin respectively. All eggs were injected solutions into yolk sac and incubated at a temperature of 37±0.5ºC. On day 3 of development, all eggs were then opened to observed morphological changes including cephalic region, limbs, caudal region and trunk. The data were analyzed by using Fisher’s Exact test to compare between group. The mortality percentage in chick embryos that exposed to curcumin 20, 40, and 60 mg/l were not statistically different when compared to non-injection group. The chick embryos exposed to curcumin 20 mg/l showed abnormal development of body curvature. The chick embryos exposed to curcumin 40 mg/l found abnormal development of cephalic region and closure failure of neural tube. Partial development of cephalic region and limb buds absence were observed in chick embryos exposed to 60 mg/l.